Prevalence of hepatitis B and hepatitis C virus infection in repeatedly transfused thalassemics in a tertiary care hospital in eastern India - Mukherjee, Kheya; Bhattacharjee, Debojyoti; Chakraborti, Goutam (International Journal of Research in Medical Sciences, 2017)
Background: Patients of thalassemia who are conventionally treated by a regular transfusion regimen are at a risk of developing transfusion transmissible infections, including hepatitis. The present study was conducted to assess the prevalence of hepatitis B and hepatitis C virus infections among repeatedly transfused thalassemia patients. Methods: A total of 207 patients of beta-thalassemia, who had received at least 10 transfusions were tested for hepatitis B surface antigen (HBsAg) and anti-HCV antibody using enzyme linked immunosorbant assay (ELISA). Results: The overall number of anti-hepatitis C antibody seropositive was 51 (24.6%) and that for hepatitis B surface antigen positives was 7 (3.38%). The prevalence rate for hepatitis B surface antigen was in agreement with average national values, but in case of anti-HCV antibodies the prevalence rate values were comparatively much higher. Conclusions: Stringent measures need to be taken on urgent basis while screening blood for anti-hepatitis C antibody and hepatitis B surface antigen including inclusion of other sensitive assay like nucleic acid test (NAT) as well as better donor recruitment.